A PHYSICAL BASIS FOR PAULING'S DEFINITION OF BOND STRENGTH - Gibbs G.V.; Rosso K.M.; Cox D.F.; Boisen Jr.M.B. (My University, 2003)
The average strength, s, of the bonded interactions comprising a cation containing oxide anion coordination polyhedron and the value of the electron density, ρ(rc), at the bond-critical points are inversely correlated with bond length. In each case, the observed bond lengths, R, were modeled with power-law expressions defined in terms of s/r and ρ(rc)/r, respectively, where r is the Periodic Table row number of the cation involved in the bonded interaction. On the basis of the close connection between bond strength and the value of the electron density at the bond-critical point, we conclude that bond strength is a direct measure of bond type; the greater its value, the greater the localization of electron density in the binding region and the greater the shared-electron covalent character of the bonded interaction.
Keywords: BOND STRENGTH; BOND NUMBER